Search for dark photons from Higgs boson decays via ZH production with a photon plus missing transverse momentum signature from pp collisions at s $$ \sqrt{s} $$ = 13 TeV with the ATLAS detector. (Tufts University. Tisch Library., 2023)
Keywords : Hadron-Hadron Scattering.; Springer Open.